2013
DOI: 10.4132/koreanjpathol.2013.47.4.332
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Expression Is Associated with Good Prognosis in Colorectal Cancer

Abstract: BackgroundSilent mating type information regulation 2 homolog 1 (SIRT1), an NAD+-dependent deacetylase, might act as a tumor promoter by inhibiting p53, but may also as a tumor suppressor by inhibiting several oncogenes such as β-catenin and survivin. Deleted in breast cancer 1 (DBC1) is known as a negative regulator of SIRT1.MethodsImmunohistochemical expressions of SIRT1, DBC1, β-catenin, surviving, and p53 were evaluated using 2 mm tumor cores from 349 colorectal cancer patients for tissue microarray.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…The present study identified an association of SIRT1 overexpression with shorter OS time and poor prognostic indicators in SCC, which was consistent with the results of previous studies (4,36,45). By contrast, certain reports have found a significant association between SIRT1 overexpression and more favorable prognosis in serous carcinoma of the ovary (46) and colorectal cancer (47,48). In the present study, Kaplan-Meier survival analysis suggested that patients with tumor invasion (P=0.043), lymph node metastasis (P<0.001), larger tumor size (P=0.047) and higher pathological T stage (P=0.001) have poorer prognoses (Fig.…”
Section: A B C Dsupporting
confidence: 80%
“…The present study identified an association of SIRT1 overexpression with shorter OS time and poor prognostic indicators in SCC, which was consistent with the results of previous studies (4,36,45). By contrast, certain reports have found a significant association between SIRT1 overexpression and more favorable prognosis in serous carcinoma of the ovary (46) and colorectal cancer (47,48). In the present study, Kaplan-Meier survival analysis suggested that patients with tumor invasion (P=0.043), lymph node metastasis (P<0.001), larger tumor size (P=0.047) and higher pathological T stage (P=0.001) have poorer prognoses (Fig.…”
Section: A B C Dsupporting
confidence: 80%
“…Presently, several paper reported that the relationship Xiu-Lai Zhang, Min-Li Chen, Sheng-Li Zhou* between Sirt1 and colorectal cancer involved in tumor malignant degree, transfer, patient survival rate and cancer cell proliferation (Kabra et al, 2009;Jung et al, 2013;Lv et al, 2014). Whether sirt1 acting as a cancer-promoting genes or a tumor suppressor gene is always a controversy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in several other cancer types, including breast, liver, and gastric cancers, overexpression of SIRT1 is associated with poor prognosis, implying a role for SIRT1 in cancer promotion [13][14][15][16]. In colon cancer, the implications of high expression levels of SIRT1 remain controversial [17][18][19][20][21]. Consistent with these in vivo observations, in vitro studies have shown context-dependent roles of SIRT1 in cancer cells [22][23][24].…”
Section: Introductionmentioning
confidence: 76%